We were all learning and doing our best: Investigating how Enabling educators promoted student belonging in a time of significant complexity and unpredictability - James, Trixie; Bond, Kerry; Kumar, Brijesh; Tomlins, Melissa; Toth, Gabriela (Journal of University Teaching and Learning Practice, 2022)
The COVID-19 pandemic impacted education provision worldwide. In Australia, the government took a proactive stance to reduce the impact of the pandemic, temporarily banning higher education students from attending university campuses. With a lockdown in place, educational institutions required a rapid shift in approaches to teaching and learning by both educators and students. Educators throughout Australia were asked to work from home and quickly transition their face-to-face (synchronous) classes into bichronous, fully online offerings. This paper reports on the experiences of 25 educators in an enabling course in a regional Australian university who were required to make this shift. These educators not only had to navigate this complex time personally, but they also had to work in their professional role with the additional responsibility of ensuring a particularly vulnerable cohort of non-traditional students felt a sense of belonging within this new educational space. Results showed that while the educators encountered a number of challenges in their transition, they also found ways to promote student belonging in the new teaching and learning environment. With a Pedagogy of Care being central to the educators’ practice, they developed strategies to create a sense of emotional engagement among students to help them feel genuinely cared for. Additionally, they were able to construct a ‘we mentality’ discourse to establish a sense of shared understanding with students around the situation they were in. This study shows that enabling educators are capable of responding creatively to a complex and unpredictable environment, finding ways to replicate their proven pedagogies of care in unfamiliar contexts and thus foster a crucial sense of belonging among enabling students. The implications of a discussion about ‘care’ and ‘belonging’ within the field of enabling education are critical at the intra-pandemic and post-pandemic times, when traditional teaching methodologies are in flux.